2020
DOI: 10.1177/0886260520926311
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Trauma Centrality and Posttraumatic Stress Among Syrian Refugees: The Impact of Cognitive Distortions and Trauma-Coping Self-Efficacy

Abstract: While research suggests that the war in Syria has led to a drastic re-evaluation of oneself and elevated psychiatric symptoms among Syrian refugees, little is known whether these psychological reactions might be influenced by maladaptive beliefs about oneself and the world and their ability to cope with the effect of the trauma. This study aimed to provide further evidence on the association between trauma centrality, posttraumatic stress, and psychiatric comorbidity, and examine whether cognitive distortions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Forty-two studies assessed PTSD and trauma-related disorders (Acarturk et al, 2018, 2021; Alpak et al, 2015; Al-Smadi et al, 2016; Aoun et al, 2019; Basheti et al, 2019; Böge et al, 2020; Borho et al, 2020; Cengiz et al, 2018; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; Demir et al, 2020; Ersahin, 2022; Fuhr et al, 2019; Georgiadou et al, 2018, 2020; Gottvall et al, 2019; Hendaus et al, 2021; Ibrahim & Hassan, 2017; Javanbakht et al, 2019; Jefee-Bahloul et al, 2014; Kazour et al, 2017; Mahmood et al, 2019; Marwa, 2016; McGrath et al, 2020; M’zah et al, 2019; Oda et al, 2021; Powell et al, 2020; Rizkalla & Segal, 2018, 2019; Röhr et al, 2020; Sagaltici et al, 2020; Sengoelge et al, 2019; Sim et al, 2018, 2019; Tekeli-Yesil et al, 2018; Tinghög et al, 2017; Uygun, 2021). The most preferred instrument to evaluate PTSD was the Harvard Trauma Questionnaire (HTQ).…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-two studies assessed PTSD and trauma-related disorders (Acarturk et al, 2018, 2021; Alpak et al, 2015; Al-Smadi et al, 2016; Aoun et al, 2019; Basheti et al, 2019; Böge et al, 2020; Borho et al, 2020; Cengiz et al, 2018; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; Demir et al, 2020; Ersahin, 2022; Fuhr et al, 2019; Georgiadou et al, 2018, 2020; Gottvall et al, 2019; Hendaus et al, 2021; Ibrahim & Hassan, 2017; Javanbakht et al, 2019; Jefee-Bahloul et al, 2014; Kazour et al, 2017; Mahmood et al, 2019; Marwa, 2016; McGrath et al, 2020; M’zah et al, 2019; Oda et al, 2021; Powell et al, 2020; Rizkalla & Segal, 2018, 2019; Röhr et al, 2020; Sagaltici et al, 2020; Sengoelge et al, 2019; Sim et al, 2018, 2019; Tekeli-Yesil et al, 2018; Tinghög et al, 2017; Uygun, 2021). The most preferred instrument to evaluate PTSD was the Harvard Trauma Questionnaire (HTQ).…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%
“…Only one study in this review assessed psychosis, and it reported a positive screening of 7.6% for psychotic disorders using the Mini International Neuropsychiatric Interview (MINI) instrument (Rizkalla & Segal, 2018). Other mental disorders or psychiatric symptoms investigated were psychological distress (Basheti et al, 2015; Borho et al, 2020; Bridekirk & Hynie, 2021; Hendaus et al, 2021; Khamis, 2022; M’zah et al, 2019; Oda et al, 2021; Saab et al, 2020; Schlechter et al, 2021; Sim et al, 2018, 2019), somatization problems (Braun-Lewensohn et al, 2019; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; McGrath et al, 2020), substance use disorders (Kazour et al, 2017; Oda et al, 2021), and eating disorder (Aoun et al, 2019).…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Event centrality has been evidenced as one of the significant correlates of post‐traumatic stress symptoms (PTSS) in populations with different traumatic events, including survivors of childhood maltreatment (Watts et al., 2021), individuals diagnosed with PTSD (Uzer et al., 2020), survivors of natural disasters (Mordeno et al., 2018), refugees (Chung & Shakra, 2020), and bereaved undergraduates (Bellet et al., 2018). Research has shown that event centrality positively correlates with PTSD symptoms, even when controlling for event severity, depression, anxiety, dissociation, self‐consciousness, and personality traits (Berntse & Rubin, 2007; Ogle et al., 2013; Vermeulen et al., 2020).…”
Section: Introductionmentioning
confidence: 99%